Bobby Woods with Mariposan - Tom Hrdiva
Title based on content of image. Caption on verso reads: "Bobbie Woods. Photo property of Mariposa Folk Festival. Please credit Tom Hrdiva. (P85). Tom Hrdiva. Bobbie Woods." Digitization possible through funding from Young Canada Works grant for the summer of 2018. We acknowledge the financial support of the Government of Canada. Nous reconnaissons l'appui financier du gouvernement du Canada.